Experimental investigation of hydrodynamic cavitation through orifices of different geometries - Rudolf Pavel; Kubina Dávid; Hudec Martin; Kozák Jiří; Maršálek Blahoslav; Maršálková Eliška; Pochylý František (EPJ Web of Conferences, 2017)
Hydrodynamic cavitation in single and multihole orifices was experimentally investigated to assess their hydraulic characteristics: loss coefficients, inception cavitation number, cavitation number for transition to supercavitation. Significant difference for singlehole and multihole orifices was observed in terms of the measured loss coefficient. It is significantly more effective to use multihole orifices, where energy dissipation is much lower.It was found that using scaling factor given by ratio of orifice thickness suggests linear behaviour of both loss coefficient and inception cavitation number. Orifices seem to be convenient choice as flow constriction devices inducing cavitation due to their simplicity.